Extraretinal Fibrovascular Proliferation in a Neonate Possibly Associated with an ESAM Gene Variant - Sadık Etka Bayramoğlu; Nihat Sayın; Mehmet Erdoğan; Sümeyra Doğan; Alper Gezdirici; Merih Çetinkaya (Türk Oftalmoloji Dergisi, 2023)

(untitled)
A female infant born with a gestational age of 35 weeks and birth weight of 2500 g was referred for ophthalmic examination on the second postnatal day. Bilateral venous dilatation and arterial tortuosity, severe extraretinal fibrovascular proliferation, and peripheral ischemia were detected. Fluorescein angiography showed profoundly delayed arteriovenous transit and peripheral avascularity. Both eyes were treated with diode laser photocoagulation and bevacizumab injection. Cranial magnetic resonance imaging (MRI) revealed hydrocephalus, ventricular dilatation, and cerebral atrophy. Her family history revealed that the patient’s brother presented to the ophthalmology outpatient clinic at postnatal 3 months with inoperable total retinal detachment and similar cranial MRI findings. No systemic or ocular findings were detected in the parents. A recent study showed that in 13 cases, including our patients, bi-allelic variants in the ESAM gene lead to a new neurodevelopmental disease whose main clinical features include impaired speech and language development, seizures, varying degrees of spasticity, ventriculomegaly, intracranial hemorrhage, and developmental delay/mental disability. Newborn siblings of children with serious pathological retinal findings should undergo a detailed ophthalmic examination as soon as possible after birth to prevent total retinal detachment, even without a diagnosis of specific inherited retinal vascular diseases. Further investigations performed in collaboration with an international network may reveal more candidate gene variants possibly related to retinopathy of prematurity-like ophthalmological findings such as extraretinal fibrovascular proliferation.